The Role of Laboratory and Radiology in Diagnosing and Monitoring Interstitial Lung Diseases - Anas Ahmad Sultan; Mohamed Abdulmajid Abduljabar; Ashwag Diab Alshammari; Wadyan Fadhy Alshammari; Abdullah Saad Almutairi; Khalid Saleh Qurayit Aljohani; Abdullatif Saad Aljohani; Tariq Ayed Alalawi; Hatem Mattar Alshammari; Mesfer Mohamad Moshabab Al-Ahmari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Interstitial lung disease (ILDs) form a group of heterogeneous pulmonary pathologies that require early diagnosis for proper management. High-resolution computed tomography (HRCT) is significant in characterizing ILD patterns, and laboratory markers serve towards disease characterization and follow-up. In spite of such significant tools, persistent barriers such as variable approaches in diagnosing and restricted multidisciplinary coordination hinder disease management. Enhancement in coordination between radiologists, pulmonologists, and laboratory professionals, along with application of sophisticated imaging and molecular diagnostics, can streamline early detection and personalized therapy, and in consequence, maximize patient care.